Penentuan Harga Pokok Produksi Dengan Pendekatan Full Costing Pada UMKM Kacang Gula Merah Di Sangatta - Nanok Fitriyadi.S; Jumri Jumri; Fatma Eka Sari; Nuuridha Matiin; Putri Aliska (Politeknik Raflesia Press, 2025)
This research aims to determine the determination of the cost of production using the full costing method in the Sangatta Brown Sugar Bean MSMEs. Based on the results of research on determining the cost of production using a full costing approach for brown sugar bean SMEs in Sangatta, the author draws conclusions. Based on the calculation of the cost of production using the full costing method, it is greater and worth IDR. 6,772,000. And from determining the selling price, the method of calculating the cost of production using the full costing method is higher, while the selling price using the full costing method is IDR 3,386/kg.